FORMULASI BIOFERTILIZER CAIR MENGGUNAKAN BAKTERI PELARUT FOSFAT INDIGENUS ASAL TANAH GAMBUT RIAU - Suci Novri Yelti; Delita Zul; Bernadeta Leni Fibriarti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Inefficient of P-uptake by plants during the application of chemical phosphorus (P) fertilizer results P-leaching to the aquatic environment. Therefore, the use of phosphate solubilizing bacteria (PSB) to enhance solubilization of P is necessary. The aims of this study were to find the best formulation in producing liquid biofertilizer which contained PSB and to analyze the storage time of liquid biofertilizer which were produced. As many as 4 selected PSB isolates (BB_UB6, BB_K9, BB_K2 and BB_HS13) were used to produce 3 combination starters. Liquid biofertilizers were produced by fermentation using three types of formulation, namely Pikovskaya's medium, coconut water enriched with 2% molasses, and tofu waste water. The quality of liquid biofertilizer was determined by calculating the PSB cells number during 0, 30, and 60 days of storage time and by measuring the liquid biofertilizer acidity. Liquid biofertilizers produced were kept at room and refrigerator temperature. The results showed that the PSB cell numbers of starter I, II and III were higher in liquid biofertilizer that was formulated with coconut water which containing 2% of molasses until 60 days of storage time. The cell numbers of PSB ranged from 7,0×1010 - 2,82×1011 CFU/ml. In general, the PSB cell number was relatively stable when liquid biofertilizer was kept at room temperature. Based on this results, it can be concluded that the best formulation to produce liquid biofertilizer was the coconut water enriched with 2% molasses.